A lung-inspired approach to scalable and robust fuel cell design. Issue 1 (25th October 2017) - Trogadas, P.; Cho, J. I. S.; Neville, T. P.; Marquis, J.; Wu, B.; Brett, D. J. L.; Coppens, M.-O.
Abstract : Lung-inspired flow fields are employed to overcome reactant homogeneity issues in PEFCs, resulting in enhanced performance and minimal pressure drop. Abstract : A lung-inspired approach is employed to overcome reactant homogeneity issues in polymer electrolyte fuel cells. The fractal geometry of the lung is used as the model to design flow-fields of different branching generations, resulting in uniform reactant distribution across the electrodes and minimum entropy production of the whole system. 3D printed, lung-inspired flow field based PEFCs with N = 4 generations outperform the conventional serpentine flow field designs at 50% and 75% RH, exhibiting a ∼20% and ∼30% increase in performance (at current densities higher than 0.8 A cm −2 ) and maximum power density, respectively. In terms of pressure drop, fractal flow-fields with N = 3 and 4 generations demonstrate ∼75% and ∼50% lower values than conventional serpentine flow-field design for all RH tested, reducing the power requirements for pressurization and recirculation of the reactants. The positive effect of uniform reactant distribution is pronounced under extended current-hold measurements, where lung-inspired flow field based PEFCs with N = 4 generations exhibit the lowest voltage decay (∼5 mV h −1 ). The enhanced fuel cell performance and low pressure drop values of fractal flow field design are preserved at large scale (25 cm 2 ), in which the excessive pressure drop of a large-scale serpentine flow field renders its use prohibitive.